Investigating The Relationship Between Health Diplomacy and Covid-19 Pandemic Containment in Nigeria - Ugochukwu David Abasilim; Esther Oiza Moses (Universitas Medan Area, 2023)
The purpose of this study was to investigate the relationship between health diplomacy and COVID-19 containment in Nigeria. The study used a qualitative method which relied on interviews with employees from the Nigeria Centre for Disease Control (NCDC), which aims to detect and respond to infectious disease outbreaks among other things. Thematic analysis and discussion were conducted on the data obtained from the interviews. The study discovered a link between Health Diplomacy and the COVID-19 pandemic. Based on the findings of the study, it was recommended that the NCDC and the Nigerian government should maintain their friendship with the foreign partners who have assisted Nigeria in containing the COVID-19 pandemic. This could be accomplished through regular meetings, conferences, and other means of communication, keeping in mind that these partners will not be available all of the time to assist Nigerians in the event of another pandemic in the future.